2020
DOI: 10.1111/jgs.16952
|View full text |Cite
|
Sign up to set email alerts
|

“At Home, with Care”: Lessons from New York City Home‐based Primary Care Practices Managing COVID‐19

Abstract: Background/Objectives COVID‐19 required rapid innovation throughout the healthcare system. Home‐based primary care (HBPC) practices faced unique challenges maintaining services for medically complex older populations for whom they needed to adapt a traditionally hands‐on, model of care to accommodate restrictions on in‐person contact. Our aim was to determine strategies used by New York City (NYC)‐area HBPC practices to provide patient care during the first wave of the COVID‐19 pandemic with the goal of inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
85
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 19 publications
3
85
0
Order By: Relevance
“…Obstacles in doctor-patient communication due to personal protective equipment and social distancing complicated the professionals' daily routine. 12,36 Some challenges were reported as well in healthcare procedures and operational functions, as reported by Franzosa et al 37 who highlighted that keeping patients "at home with care" during the pandemic included both patient-faced and practice-faced challenges. These dynamics created a high emotional burden in home palliative care professionals, according to the literature showing how continuous changes, overwork, and the fear of infection may negatively impact on the physical and psychological health of healthcare professionals, leading to anxiety, depression, burnout syndrome, and other mental health concerns.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Obstacles in doctor-patient communication due to personal protective equipment and social distancing complicated the professionals' daily routine. 12,36 Some challenges were reported as well in healthcare procedures and operational functions, as reported by Franzosa et al 37 who highlighted that keeping patients "at home with care" during the pandemic included both patient-faced and practice-faced challenges. These dynamics created a high emotional burden in home palliative care professionals, according to the literature showing how continuous changes, overwork, and the fear of infection may negatively impact on the physical and psychological health of healthcare professionals, leading to anxiety, depression, burnout syndrome, and other mental health concerns.…”
Section: Discussionmentioning
confidence: 97%
“…6,37,43 The healthcare team represents another resource. As reported in a study on home care professionals, 37 our findings confirmed that team connections played an essential role for the home palliative care professionals, both in terms of the clinical management of patients and their emotional support. However, other findings on hospital staff reported a lack of communication between colleagues and challenging relationships within the staff during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations